Redefining Local Budget Efficiency through Green Accounting - Freke Jimmi Johanis; Hedy Desiree Rumambi; Ivoletti Merlina Walukow; Stevie Kaligis; Jolly Lucky Raymond Turangan; Andreuw Kristian Pantow (Jurusan Akuntansi Politeknik Negeri Malang, 2026)
Purpose: This study investigates the contribution of green accounting to the efficiency of budget improvement at the North Minahasa Regency Finance and Asset Agency following Government Instruction Number 1 of 2025.Method: This was a descriptive qualitative study.Results: The results showed that the efficiency rate of budgets achieved a figure of 64.38%, which is categorized as efficient; wherein, this was supported by strategies such as the implementation of document digitization and also reduction in office supply use.Novelty: This research is unique in its application of green accounting in local government budget management. Contribution: This research adds to the literature by showing that green accounting practices can increase budget efficiency in local government institutions. Abstrak : Mendefinisikan Ulang Efisiensi Anggaran Lokal melalui Akuntansi Hijau Tujuan: Penelitian ini mengkaji praktik akuntansi hijau berkontribusi meningkatkan efisiensi anggaran di Badan Keuangan dan Aset Kabupaten Minahasa Utara setelah diterbitkannya Instruksi Presiden Nomor 1/2025.Metode: Studi ini menggunakan pendekatan deskriptif kualitatif.Hasil: Hasil menunjukkan tingkat efisiensi anggaran sebesar 64,38%, yang dianggap efisien, didorong oleh strategi termasuk penerapan digitalisasi dokumen dan pengurangan penggunaan perlengkapan kantor.Kebaruan: Keunikan penelitian ini terletak pada penerapan akuntansi hijau dalam pengelolaan anggaran pemerintah daerah.Kontribusi: Penelitian ini berkontribusi pada literatur dengan menunjukkan bagaimana praktik akuntansi hijau dapat meningkatkan efisiensi anggaran pada instansi pemerintah daerah.